Entrepreneurship and Economic Growth in Spanish and Portuguese Regions - Emilia Vázquez; Sofia Gomes; Elvira Vieira (European Regional Science Association (ERSA), 2010)
The theory of economic growth covers institutional market and company internal factors that explain the disparities in well-being among countries, in a given period. It also questions welfare growth dynamics that leads to convergence or divergence of per capita wealth levels. (Solow, 1956-1957; Grilliches, 1979; Romer, 1986, 1990; Lucas, 1988; Barro, 1999; Barro e Sala-i-Martin, 1991 e 1992; Rebelo, 1991, Mankiw, Romer e Weil, 1992). The economic study of entrepreneurship is concerned with identifying factors that influence the dynamics of business creation and the consequences of these dynamics on economic growth. (Acs e Armington, 2006; Audretsch e Keilbach, 2004; Audretsch, Keilbach, Lehmann, 2006; Carree e Thurik, 2006; Van Stel, 2006). There are several studies that establish a direct relationship between entrepreneurship and economic growth. Other empirical works address an indirect relationship through the establishment of an interaction between entrepreneurship and employment rate growth. With a similar approach to other works that relate entrepreneurial activity (Petrakis, 2004; Audretsch and Keilbach 2004; Wong, Ho e Autio, 2005; Acs e Varga, 2005; Stam, Suddle, Hessels e Van Stel, 2006; Van Stel, Storey e Thurik, 2009; Barros e Pereira 2008; Salas y Sánchez-Asín, 2008) this paper analyzes the effect of entrepreneurship on growth on Spanish and Portuguese regions
Keywords: 330